Self-assembly of mitochondria-specific peptide amphiphiles amplifying lung cancer cell death through targeting the VDAC1-hexokinase-II complex - Liu, Dan; Angelova, Angelina; Liu, Jianwen; Garamus, Vasil M; Angelov, Borislav; Zhang, Xinlei; Li, Yawen; Feger, Guillaume; Li, Na; Zou, Aihua (Journal of materials chemistry. B, 2019)
Mitochondria-targeting peptides represent an emergent tool for cancer inhibition. Here supramolecular assemblies of novel amphiphilic cell-penetrating peptides for targeting cancer cell mitochondria are reported. The employed strategy aims at amplifying the apoptotic stimuli by weakening the mitochondrial VDAC1 (voltage-dependent anion channel-1)-hexokinase-II (HK-II) interaction. Peptide engineering is performed with the N-terminus of the HK-II protein, which binds to VDAC1. First, a designed positively charged segment (pKV) is anchored to the specific 15 amino acid sequence (MIASHLLAYFFTELN) to yield a cell-penetrating peptide (pHK-pKV). Second, a lipid chain (Pal) is conjugated to the N-terminus of pHK-pKV in order to enhance the intracellular delivery of the HK-II scaffold. The self-assembly properties of these two synthetic peptides are investigated by synchrotron small-angle X-ray scattering (BioSAXS) and cryogenic transmission electron (cryo-TEM) imaging, which evidence the formation of nanoassemblies of ellipsoid-like shapes. Circular dichroism (CD) spectroscopy demonstrates the induction of partial α-helical structures in the amphiphilic peptides. Confocal microscopy reveals the specific mitochondrial location of Pal-pHK-pKV assemblies in human non-small cell lung cancer (NSCLC) A549 cells. The cytotoxicity and apoptotic studies indicate the enhanced bioactivity of Pal-pHK-pKV self-assembled reservoirs, which cause massive A549 cell death with regard to pHK-pKV. Of significance, Pal-pHK-pKV treatment of non-cancerous NCM460 cells resulted in substantially lower cytotoxicity. The results demonstrate the potential of self-assembled lipo-peptide (HK-II-derived) conjugates as a promising strategy in cancer therapy.
Keywords: Mitochondria; nádory plic; Lipopeptides; Lung Neoplasms; napětím ovládaný aniontový kanál 1; Cell Death; buněčná smrt; Surface-Active Agents; Drug Delivery Systems; lipidy; lidé; povrchově aktivní látky; Humans; hexokinasa; buňky A549; Voltage-Dependent Anion Channel 1; Lipids; penetrační peptidy; lipopeptidy; A549 Cells; Cell-Penetrating Peptides; lékové transportní systémy; mitochondrie; Hexokinase